2002
DOI: 10.1063/1.1435068
|View full text |Cite
|
Sign up to set email alerts
|

Improved surface imaging with a near-field scanning microwave microscope using a tunable resonator

Abstract: We report a microwave surface imaging technique using a near-field scanning microwave microscope with a tunable resonance cavity. By tuning the resonance cavity, we could demonstrate improved sensitivity and spatial resolution of the topographic image of YBa2Cu3Oy thin films on MgO substrates. By measuring the shift of resonant frequency and the change of quality factor, we obtained near-field scanning microwave images with a spatial resolution better than 4 μm at an operating frequency of f=1–1.5 GHz. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…As the probe scans over the sample surface, variation of the local sample property results in changes of the impedance between the probe tip and ground, which are then detected and recorded to form near-field images, with a spatial resolution comparable to the curvature of the tip apex. Due to the potential applications in electron physics, material science, and biological studies, near-field scanning microwave microscopes have been demonstrated by several groups as scientifically useful instruments [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As the probe scans over the sample surface, variation of the local sample property results in changes of the impedance between the probe tip and ground, which are then detected and recorded to form near-field images, with a spatial resolution comparable to the curvature of the tip apex. Due to the potential applications in electron physics, material science, and biological studies, near-field scanning microwave microscopes have been demonstrated by several groups as scientifically useful instruments [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a higher Q causes a larger slope of the reflectivity Sn and, thus, increasing the Q of resonator will increase S x . The minimum detectable detector output power AP mi of the NSMM can be written as [13,16], &P out =MS x S d P in (1) zJPom is directly correlated with the sensitivity of the NSMM. Thus, to achieve the largest possible sensitivity, both S d and S x must be maximized.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a variety of scanning probe techniques have been developed for microwave-and millimeter-wave ranges [1][2][3][4][5][6][7][8][9][10][11][12][13]. In order to achieve the largest possible sensitivity and spatial resolution of the NSMM, both the quality of the resonator and the sensitivity of the probe must be maximized [1,13]. A high quality factor of the resonator permits measurement of relatively small variation in electrical properties of samples.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Unlike the conventional metal-wire probe backed by a relatively massive resonator, 3,4,7,8 the cantilever probe is scalable and significantly miniaturized for better resolution. For better sensitivity, metal traces rather than lossy doped Si lines 14,15 were patterned on nitride cantilevers.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] The non-local stray field contribution not only compromises the spatial resolution but also complicates the quantitative analysis of tip-sample interaction. Calibration of the microscope output using bulk samples [9][10][11] is therefore difficult, if not totally impossible.…”
mentioning
confidence: 99%